USE OF DIFFERENT KIND BIOCIDES IN WATERTREATMENT - Сусь, М. О.; Мітченко, Т. Є. (WATER AND WATER PURIFICATION TECHNOLOGIES. SCIENTIFIC AND TECHNICAL NEWS, 2011)
An overview and classification of up-to-date biocidal reagents for different purpose water disinfection are given. The action spectrum, mode of action, features, advantages and disadvantages of each of biocide are considered. The list of most known manufacturers and suppliers of biocides for water treatment is presented.